IMPLEMENTATION OF AGRARIAN LAW IN NATURAL RESOURCE MANAGEMENT IN TOMOHON: Implementasi Hukum Agraria dalam Pengelolaan Sumber Daya Alam di Tomohon - Pingkan Dewi Kaunang (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to examine the implementation of agrarian law in Tomohon City, focusing on land status, challenges in enforcement, the impact on natural resource management, and the role of the community in these processes. The research used qualitative methods, including interviews, observations, and document analysis, to gather data on the current agrarian law implementation. The results indicate that while Tomohon has comprehensive regulations, such as Regional Regulation No. 12 of 2013 on Natural Resource Management, the actual implementation remains limited to specific areas. Coordination between relevant institutions, such as the Land Office, the Environment Agency, and the Public Works and Spatial Planning Agency, is weak, hindering effective land and resource management. Additionally, land use changes, particularly the conversion of agricultural land to residential and industrial areas, have led to agrarian conflicts. Another key challenge is the insufficient supervision of land use, allowing violations of agrarian law, such as unauthorized land utilization. Despite some positive impacts on maintaining agricultural land, land conversion has caused significant environmental damage. Moreover, the community’s understanding of agrarian law is still low, which limits their participation in land and resource management. Based on these findings, this study recommends enhancing supervision, improving coordination between government agencies, and increasing public awareness and participation in agrarian decision-making processes. These efforts are essential to improving agrarian law enforcement and ensuring sustainable land and resource management in Tomohon City. The findings contribute to the development of more effective agrarian policies in both urban and rural areas.